2006
DOI: 10.1364/ao.45.003760
|View full text |Cite
|
Sign up to set email alerts
|

Applications of quantum dots in optical fiber luminescent oxygen sensors

Abstract: The potential applications of luminescent semiconductor nanocrystals to optical oxygen sensing are explored. The suitability of quantum dots to provide a reference signal in luminescence-based chemical sensors is addressed. A CdSe-ZnS nanocrystal, with an emission peak at 520 nm, is used to provide a reference signal. Measurements of oxygen concentration, which are based on the dynamic quenching of the luminescence of a ruthenium complex, are performed. Both the dye and the nanocrystal are immobilized in a sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 22 publications
0
31
0
Order By: Relevance
“…In the next step the radius of QDs was varied from 1 nm to 30 nm. To carry out our simulations, we set the carrier density to = 3×10 22 m −3 and the damping rate as all the relaxation rates = 5 ps −1 [67][68][69]. Also, the refractive index of GaAs was set as constant value = 3.2.…”
Section: Resultsmentioning
confidence: 99%
“…In the next step the radius of QDs was varied from 1 nm to 30 nm. To carry out our simulations, we set the carrier density to = 3×10 22 m −3 and the damping rate as all the relaxation rates = 5 ps −1 [67][68][69]. Also, the refractive index of GaAs was set as constant value = 3.2.…”
Section: Resultsmentioning
confidence: 99%
“…However, because a low permeability matrix was used, photodegradation of the Ru(dpp) was very small. It has already been demonstrated that, in spite of introducing a reduced sensitivity, doped non-hydrolitic sol-gel matrixes can provide for very photostable oxygen and temperature sensors [34,37].…”
Section: Resultsmentioning
confidence: 99%
“…Other possibilities of QDs improving the performance of oxygen sensors were recently addressed [148]. By using a sol-gel prepared SiO 2 sample doped with CdSe/ZnS QDs, with low oxygen permeability, combined with an oxygen sensing film, it was possible to implement a ratiometric reference scheme.…”
Section: Optical Fiber Sensingmentioning
confidence: 99%